Attractiveness and Facial Competence Bias Face‐Based Inferences of Candidate Ideology. Issue 3 (24th March 2015) - Herrmann, Michael; Shikano, Susumu
Abstract : Can voters infer candidates' political orientations from their faces? We report evidence that observers make systematic judgment errors, ascribing their own political views to attractive or competent‐looking candidates. Subjects judged headshot images of student candidates running in university elections (Experiment 1), as well as professional politicians from state election races in Germany (Experiment 2), according to whether the person(s) displayed held ideologically leftist or rightist views. While prediction accuracy was above chance level in both experiments, candidate attractiveness (Experiment 1) and perceived competence (Experiment 2) increased a subject's likelihood of attributing her political views to a candidate. These findings suggest that the value of face‐based inferences in choosing the candidate who best represents one's views is more limited than previously assumed. They also suggest that good looks may help extremist candidates in presenting themselves as more moderate.